Neuropathy after alcohol withdrawal - Gardner, A. J. (1972)
Three probable cases of neuropathy in alcoholics are described. They are very atypical for three reasons. First, each developed an acute asymmetrical neuropathy for the first time well after ceasing to drink, and after routine saturation with the vitamin B group. Secondly, none had previously suffered from neuropathy while still drinking. If this puzzling reversal of the usual order of clinical events has been noticed before, no record has been found in the literature. Further study by psychiatrists treating alcoholics aided by their neurological colleagues is suggested.